Enhanced composite proton exchange membrane based on hydrophobic phase modification and preparation method thereof
By introducing fluorinated SiO2 nanoparticles and expanded polytetrafluoroethylene framework into perfluorosulfonic acid resin, hydrophobic phase modification of perfluorosulfonic acid resin was achieved, solving the problems of mechanical properties and proton conductivity, and improving the overall performance of composite proton exchange membrane.
Patent Information
- Application Number
- CN202511381667.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-25
- Publication Date
- 2026-02-10
AI Technical Summary
Existing composite proton exchange membranes have low crystallinity of the hydrophobic phase in perfluorosulfonic acid resin, resulting in insufficient mechanical support. The high swelling rate of the hydrophilic region causes microcracks, affecting mechanical properties and proton conductivity.
Fluorinated SiO2 nanoparticles are composited with perfluorosulfonic acid resin. Ordered microphase separation is achieved through hydrophobic interactions. Expanded polytetrafluoroethylene porous framework is used to form a high-strength physical anchoring interface. Fluorinated-SiO2 nanoparticles act as a rigid core to transfer stress and inhibit the slippage of perfluorosulfonic acid resin segments. Combined with hydrophilic silanol groups, water molecules are locked in to improve proton conductivity.
It significantly improves the tensile strength, dimensional stability, and proton conductivity of the proton exchange membrane, thereby enhancing the overall performance of the membrane.
Smart Images

Figure CN121506988A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the technical field of fuel cell diaphragm, in particular to an enhanced composite proton exchange membrane based on hydrophobic phase modification and a preparation method thereof. BACKGROUND
[0002] As a core component of a fuel cell, a proton exchange membrane (PEM) mainly serves to conduct protons and isolate reaction gases, and the performance of the PEM directly affects the application performance of the fuel cell. A perfluorosulfonic acid resin membrane, as the most widely used PEM at present, is limited in further development due to its high price and low mechanical performance.
[0003] In order to prepare a high-strength proton exchange membrane, some researchers have proposed a composite proton exchange membrane preparation strategy, that is, a polymer substrate or a functional filler is combined with a perfluorosulfonic acid resin, so that the amount of the perfluorosulfonic acid resin is reduced, the cost is reduced, and the mechanical performance of the proton membrane is enhanced.
[0004] For example, the invention patent CN119381483 A discloses a composite proton exchange membrane and a preparation method thereof. The perfluorosulfonic acid and the para-aramid nanofiber are combined by a papermaking method, and then perfluorosulfonic acid solution is coated on both sides to obtain a composite proton exchange membrane, so as to improve the thermal stability, dimensional stability, mechanical strength and anti-swelling property of the proton exchange membrane while ensuring high proton conductivity. The invention patent CN111234244 B discloses a hyperbranched polymer adhesive, a proton exchange membrane and a preparation method thereof. The invention uses a hyperbranched polymer adhesive to effectively realize firm combination between perfluorosulfonic acid molecular chains, thereby greatly improving the mechanical strength of the perfluorosulfonic acid membrane and enhancing the proton conductivity of the membrane. The invention patent CN11334748 A discloses a preparation method of an enhanced proton exchange membrane based on a surface sol-gel modified polymer skeleton. The polymer enhanced skeleton is modified by dopamine, then zirconium oxide is deposited on the modified polymer skeleton, and finally sulfonic acid resin is coated on both sides of the skeleton. After drying, an enhanced proton exchange membrane based on a surface modified polymer skeleton is obtained. The invention patent CN119994128 A discloses a preparation process of a composite enhanced perfluorosulfonic acid proton exchange membrane. The membrane-forming liquid is coated on a glass plate, then polytetrafluoroethylene is evenly coated on the membrane-forming liquid, then the membrane-forming liquid is coated on the surface again, and a composite enhanced perfluorosulfonic acid proton exchange membrane is obtained after heat treatment and post-treatment.
[0005] However, the above strategy relies on physical compounding, and rarely regulates the microphase separation behavior from the intrinsic structure of perfluorosulfonic acid resin. Perfluorosulfonic acid resin is composed of hydrophobic polytetrafluoroethylene skeleton (-CF2-) and hydrophilic sulfonic acid group (-SO3H), and its mechanical properties depend on the hydrophobic and hydrophilic regions. The lower crystallinity in the hydrophobic phase weakens the mechanical support, and the high swelling rate of the two hydrophilic regions induces microcracks. SUMMARY
[0006] In order to solve the above technical problems existing in the prior art, the present application provides a preparation method of a reinforced composite proton exchange membrane based on hydrophobic phase modification.
[0007] A preparation method of a reinforced composite proton exchange membrane based on hydrophobic phase modification, comprising the following steps: (1) Preparation of nano filler: ammonia is added to anhydrous ethanol solvent, stirred uniformly, then tetraethyl orthosilicate is added, and SiO2 nanoparticle suspension is obtained; (2) Fluorinated modifier is added to the SiO2 nanoparticle suspension, stirred and reacted, taken out and washed with anhydrous ethanol, centrifuged, and dried to obtain fluorinated-SiO2 nanoparticles; The fluorinated modified silica nanoparticles (fluorinated-SiO2) need to ensure the amount of modification grafting and ensure a certain hydrophobicity, so that the fluorinated-SiO2 can be effectively dispersed in the perfluorosulfonic acid resin solution; (3) Preparation of composite proton exchange membrane: disperse fluorinated-SiO2 in perfluorosulfonic acid solution, effectively disperse fluorinated-SiO2 in perfluorosulfonic acid resin solution by ultrasonic treatment combined with mechanical stirring method, degassing treatment, obtain mixed membrane liquid, coating the membrane liquid on both sides of the expanded polytetrafluoroethylene base film, standing to make the membrane liquid completely fill the porous skeleton, then high temperature curing, obtaining the composite proton exchange membrane.
[0008] The structure of the rigid additive is shown in the schematic diagram Figure 1 .
[0009] The preparation method of the nano filler adopts Stöber method to prepare nano silica particles, and then fluorination modification is performed to give the nano particles certain hydrophobic properties.
[0010] Further, the volume of anhydrous ethanol is 20-180 mL, the content of ammonia is 0.1-10 mL, the content of tetraethyl orthosilicate is 0.2-50 mL, and the stirring time is 1-24 h.
[0011] Further, the fluorinated modifier is any one or more of 1H, 1H, 2H, 2H-perfluorooctyl acrylate, perfluorooctyltrichlorosilane, and trimethylchlorosilane mixed in any ratio.
[0012] Further, the step (2), the fluorinated modifier content is 0.1-2 mL, the centrifugal rate is 8000 rpm, the time is 5 min, the drying temperature is 70℃, and the drying time is 12 h.
[0013] Further, the step (3), wherein the expanded polytetrafluoroethylene-based film has a thickness of 8-15 μm and a porosity of >60%.
[0014] Further, the perfluorosulfonic acid resin solution in the step (3) has an EW value of 900-1000 g / mol and a solid content of 20 wt%.
[0015] Further, the step (3) has an ultrasonic power of >40 kHz, a stirring speed of >1000 rpm, and a time of 30-120 min.
[0016] Further, the step (3) has a fluorinated-SiO2addition amount of 0.05-1 wt%, and a solid content in the perfluorosulfonic acid resin solution of 14-20 wt%.
[0017] Further, the step (3) has a defoaming time of 12-24 h and a temperature of 25℃.
[0018] Further, the step (3) has a standing time of 1-10 min, a curing temperature of 110-180℃, and a curing time of 2-10 min.
[0019] Further, the step (3) has a thickness of 8-20 μm of the finally obtained composite proton exchange membrane. The enhanced composite proton exchange membrane based on the hydrophobic phase modification is prepared by the above method.
[0020] Compared with the prior art, the technical effects of the present application are embodied in: The present application synthesizes a fluorinated modified SiO2nanoparticle, which is wrapped by a hydrophobic perfluoro shell, and is compatible with the hydrophobic main chain of perfluorosulfonic acid resin through fluorine-fluorine interaction, promoting the ordered microphase separation of the hydrophobic domain of perfluorosulfonic acid resin; at the same time, the expanded polytetrafluoroethylene porous skeleton forms a high-strength physical anchoring interface due to its chemical composition (-CF2-) similar to the hydrophobic segment of perfluorosulfonic acid resin. On this basis, the fluorinated-SiO2rigid core as a nanofiller inhibits the slip of perfluorosulfonic acid resin segments through stress transfer, and cooperates with the ePTFE skeleton to realize a triple enhancement mechanism (as shown in the formula). Figure 2 In addition, the hydrophilic silicon hydroxyl group (-SiOH) of the fluorinated-SiO2core can form strong hydrogen bonds with water molecules, which can firmly lock water molecules at low humidity, and significantly improve the proton conductivity. BRIEF DESCRIPTION OF DRAWINGS
[0021] Figure 1 This is a schematic diagram of the rigid additive structure of the present invention.
[0022] Figure 2 This is a schematic diagram of the structure of the composite proton exchange membrane prepared according to the present invention. Detailed Implementation
[0023] The present invention will be described in detail below with reference to embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the present invention in any way. It should be noted that those skilled in the art can make several adjustments and improvements without departing from the concept of the present invention. These all fall within the protection scope of the present invention.
[0024] Unless otherwise specified, all materials and instruments used in the following embodiments are commercially available.
[0025] Preparation of fluorinated SiO2 nanoparticles: 6 mL of ammonia water was added to 120 mL of anhydrous ethanol and stirred until homogeneous. Then, 20 mL of tetraethyl silicate was added to the mixture, and stirring was continued for 12 h. Next, 1 mL of 1H,1H,2H,2H-perfluorooctyl acrylate was slowly added, and the reaction was allowed to proceed for 6 h. Finally, the mixture was centrifuged at 8000 rpm for 5 min, repeated three times, washed with ethanol, and the particles were dried under vacuum at 70 °C and collected for later use.
[0026] Preparation of perfluorosulfonic acid resin solution: Weigh 350 g of 20 wt% solid content perfluorosulfonic acid resin solution raw material, mix with 150 g of anhydrous ethanol, stir overnight, and dilute to 14 wt% solid content perfluorosulfonic acid resin solution for later use.
[0027] Example 1 This embodiment relates to a method for preparing an enhanced composite proton exchange membrane based on hydrophobic phase modification, the specific steps of which are as follows: (1) Weigh 0.7 g of fluorinated-SiO2 nanoparticles and add them to 500 g of perfluorosulfonic acid resin solution. Stir the solution with ultrasonic power of 50 kHz and stirring speed of 1100 rpm overnight. Prepare a 1 wt% perfluorosulfonic acid resin mixture. (2) Take a certain amount of the mixture from step (1) above and coat it onto the glass substrate. Then, cover the perfluorosulfonic acid resin mixture with the expanded polytetrafluoroethylene film fixed around the perimeter. Next, take a certain amount of the perfluorosulfonic acid resin mixture and coat it onto the base film, then immerse it for 5 minutes. Place the composite glass substrate in an oven and cure it at 120°C for 5 minutes. The composite proton exchange membrane can then be obtained.
[0028] Example 2 This embodiment relates to a method for preparing an enhanced composite proton exchange membrane based on hydrophobic phase modification, the specific steps of which are as follows: (1) Weigh 2.1 g of fluorinated-SiO2 nanoparticles and add them to 500 g of perfluorosulfonic acid resin solution. Stir the mixture ultrasonically overnight at a power of 50 kHz and a stirring speed of 1100 rpm. Prepare a 3 wt% perfluorosulfonic acid resin mixture. (2) Take a certain amount of the mixture from step (1) above and coat it onto the glass substrate. Then, cover the perfluorosulfonic acid resin mixture with the expanded polytetrafluoroethylene film fixed around the perimeter. Next, take a certain amount of the perfluorosulfonic acid resin mixture and coat it onto the base film, then immerse it for 5 minutes. Place the composite glass substrate in an oven and cure it at 120°C for 5 minutes. The composite proton exchange membrane can then be obtained.
[0029] Example 3 This embodiment relates to a method for preparing an enhanced composite proton exchange membrane based on hydrophobic phase modification, the specific steps of which are as follows: (1) Weigh 3.5 g of fluorinated-SiO2 nanoparticles and add them to 500 g of perfluorosulfonic acid resin solution. Stir the solution with ultrasonic power of 50 kHz and stirring speed of 1100 rpm overnight. Prepare a 5 wt% perfluorosulfonic acid resin mixture. (2) Take a certain amount of the mixture from step (1) above and coat it onto the glass substrate. Then, cover the perfluorosulfonic acid resin mixture with the expanded polytetrafluoroethylene film fixed around the perimeter. Next, take a certain amount of the perfluorosulfonic acid resin mixture and coat it onto the base film, then immerse it for 5 minutes. Place the composite glass substrate in an oven and cure it at 120°C for 5 minutes. The composite proton exchange membrane can then be obtained.
[0030] Example 4 This embodiment relates to a method for preparing an enhanced composite proton exchange membrane based on hydrophobic phase modification, the specific steps of which are as follows: (1) Weigh 7 g of fluorinated SiO2 nanoparticles and add them to 500 g of perfluorosulfonic acid resin solution. Stir the mixture ultrasonically overnight at a power of 50 kHz and a stirring speed of 1100 rpm. Prepare a 10 wt% perfluorosulfonic acid resin mixture. (2) Take a certain amount of the mixture from step (1) above and coat it onto the glass substrate. Then, cover the perfluorosulfonic acid resin mixture with the expanded polytetrafluoroethylene film fixed around the perimeter. Next, take a certain amount of the perfluorosulfonic acid resin mixture and coat it onto the base film, then immerse it for 5 minutes. Place the composite glass substrate in an oven and cure it at 120°C for 5 minutes. The composite proton exchange membrane can then be obtained.
[0031] Comparative Example 1 A certain amount of perfluorosulfonic acid resin solution was weighed and coated onto a glass substrate. The glass substrate was then placed in an oven and cured at 120°C for 5 minutes. The comparative sample composite proton exchange membrane 1 was obtained.
[0032] Comparative Example 2 2.1 g of fluorinated SiO2 nanoparticles were added to 500 g of perfluorosulfonic acid resin solution and ultrasonically stirred overnight at a power of 50 kHz and a stirring speed of 1100 rpm. A 3 wt% perfluorosulfonic acid resin mixture was prepared. This mixture was then coated onto a glass substrate, which was subsequently placed in an oven and cured at 120°C for 5 min. This yielded the control sample composite proton exchange membrane 2.
[0033] Comparative Example 3 A certain amount of perfluorosulfonic acid resin solution was weighed and coated onto a glass substrate. Then, an expanded polytetrafluoroethylene (PTFE) film, fixed around the perimeter, was placed over the perfluorosulfonic acid resin mixture. Another amount of the perfluorosulfonic acid resin mixture was then measured and coated onto the base film, and the mixture was immersed for 5 minutes. The composite glass substrate was then placed in an oven and cured at 120°C for 5 minutes. This yielded the comparative composite proton exchange membrane 3.
[0034] The performance tests of the examples and comparative examples are shown in Table 1.
[0035] The mechanical properties of the composite proton exchange membrane were analyzed using an electronic universal testing machine (UTM4204). The sample size was 80 mm × 10 mm, and the testing rate was 100 mm / min. The longitudinal and transverse swelling rates of the composite proton exchange membrane at 25℃ were measured using a thickness gauge and calipers, with an immersion time of 1 h. The proton conductivity of the composite proton exchange membrane at 90% RH and a temperature of 25℃ was measured using an electrochemical workstation (AUT85265).
[0036] The test results are shown in Table 1.
[0037] Table 1
[0038] analyze: As can be seen from the table above, the embodiments of the present invention achieve the following technical effects: Comparing Comparative Examples 1, 2, and 3, it can be seen that introducing fluorinated SiO2 nanoparticles and expanded polytetrafluoroethylene porous frameworks can effectively enhance the tensile strength of the proton exchange membrane and improve its dimensional stability. Comparing Comparative Examples 2 and 3, since SiO2 nanoparticles themselves contain a large number of hydrophilic hydroxyl groups, they can increase the wettability of the proton exchange membrane, promote proton conduction, and thus improve the conductivity of the proton exchange membrane.
[0039] Comparison of Comparative Examples 2 and 3 with the Examples shows that the simultaneous introduction of fluorinated-SiO2 nanoparticles and expanded polytetrafluoroethylene porous framework, combined with perfluorosulfonic acid resin, can further improve the tensile strength, dimensional stability and proton conductivity of the proton exchange membrane.
[0040] Comparing Examples 1 to 4, Example 4 had a higher amount of fluorinated-SiO2 nanoparticles added, which led to the aggregation of nanoparticles in the perfluorosulfonic acid resin, resulting in a decrease in the tensile strength, dimensional stability and proton conductivity of the proton exchange membrane.
[0041] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, or alterations made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing an enhanced composite proton exchange membrane based on hydrophobic phase modification, characterized in that, Includes the following steps: (1) Preparation of nanofillers: Ammonia water was added to anhydrous ethanol solvent and stirred evenly. Then tetraethyl silicate was added to obtain a suspension of SiO2 nanoparticles. (2) Add the fluorinated modifier to the SiO2 nanoparticle suspension, stir to react, take it out, wash with anhydrous ethanol, centrifuge, and dry to obtain fluorinated-SiO2 nanoparticles. (3) Preparation of composite proton exchange membrane: Fluorinated SiO2 is dispersed in perfluorosulfonic acid solution. By ultrasonic treatment combined with mechanical stirring, fluorinated SiO2 is effectively dispersed in perfluorosulfonic acid resin solution. After degassing treatment, a mixed membrane preparation solution is obtained. The membrane preparation solution is coated on both sides of the expanded polytetrafluoroethylene membrane. After standing, the membrane preparation solution is completely filled into the porous framework. Then, it is cured at high temperature to obtain composite proton exchange membrane.
2. The preparation method according to claim 1, characterized in that, The volume of anhydrous ethanol is 20-180 mL, the ammonia content is 0.1-10 mL, the tetraethyl silicate content is 0.2-50 mL, and the stirring time is 1-24 h.
3. The preparation method according to claim 1, characterized in that, The fluorinated modifier is any one or more of 1H,1H,2H,2H-perfluorooctyl acrylate, perfluorooctyl trichlorosilane, and trimethylchlorosilane, mixed in any proportion.
4. The preparation method according to claim 1, characterized in that, In step (2), the fluorinated modifier content is 0.1-2 mL, the centrifugation rate is 8000 rpm, the time is 5 min, the drying temperature is 70℃, and the drying time is 12 h.
5. The preparation method according to claim 1, characterized in that, In step (3), the expanded polytetrafluoroethylene film has a thickness of 8-15 μm and a porosity of >60%.
6. The preparation method according to claim 1, characterized in that, The perfluorosulfonic acid resin solution in step (3) has an EW value of 900~1000 g / mol and a solid content of 20 wt%.
7. The preparation method according to claim 1, characterized in that, In step (3), the ultrasonic power is >40kHz, the stirring speed is >1000 rpm, and the time is 30-120 min.
8. The preparation method according to claim 1, characterized in that, The amount of fluorinated SiO2 added in step (3) is 0.05-1 wt%, and the solid content in the perfluorosulfonic acid resin solution is 14-20 wt%.
9. The preparation method according to claim 1, characterized in that, The degassing time in step (3) is 12-24 h, and the temperature is 25℃.
10. An enhanced composite proton exchange membrane based on hydrophobic phase modification prepared by the preparation method according to any one of claims 1-9.
Citation Information
Patent Citations
Hyperbranched polymer adhesives, proton exchange membranes and their preparation methods
CN111234244B
Composite proton exchange membrane and preparation method thereof
CN119381483A
Preparation process of composite enhanced perfluorosulfonic acid proton exchange membrane
CN119994128A
Technique for molding new type proton exchange membrane
CN101050285A
Fiber and modified silica-doped fluorine-containing ion film and preparation method thereof
CN101851382A